Improvement of morphological properties of kenaf (Hibiscus cannabinus L.) by adding nutrients - Salih, Rabar Fatah; Abdan, Khalina; Wayayok, Aimrun; Hashim, Norhashila (2015)
Kenaf 4383 variety was planted at Taman Pertanian Universiti at Universiti Putra Malaysia. The objective of this study is to investigate the influence of different dosage of potassium, boron and zinc on the fiber morphology of kenaf bast fiber. These fertilizers were also applied two times based on the type of fertilizers and growth stages. The average of the bundle fiber length was by 8.03 cm. It was obtained when potassium, boron and zinc were added at the rate of 150, 1.5 and 5 kg/ha, respectively. Despite, the results of other morphological features of the bast fiber were produced by following maceration method such as: the longest single fiber length was recorded as 2.30 mm when potassium and zinc were added at the rate of 100 and 5 kg/ha, respectively. The biggest single fiber diameter and also the cell wall thickness according to the results of this current study were recorded as 20.60 μm and 6.20 μm, respectively when potassium and boron were applied at the rate of 100 and 1.5 kg/ha, respectively. The combination of boron and zinc at the rate of 1.5 and 5 kg/ha, respectively produced the lumen diameter which was 8.45 μm. Statistical analysis indicates that the mixed between all nutrients as used in this present research is greatly beneficial for improving quality properties of the bast kenaf fiber that is used for varied engineering applications.